Critical Thinking, Postmodernism, and Rational Evaluation - Donald L. Hatcher (Informal Logic, 1994)
In this paper, after showing how the postmodern critiques of Enlightenment rationality apply to critical thinking, I argue that a critical discussion on any subject must assume specific principles of rationality. I then show how these principles can be used to critique and reject postmodern claims about the contextual nature of rationality.